The Analyze Effect Of Service Marketing Mixes On Purchase Decisions Consumers Which Mediation By Consumer Trust To Use Service Of JNE Main Branch Medan - Nur Fatiha Utami Nasution; Mesra B; Toyib Daulay; Elfitra Desy Surya; Nur Afrina Siregar (Yayasan Multidimensi Kreatif, 2023)
This research was carried out in the JNE Main Branch in Medan where this study was conducted to determine how the influence of the service marketing mix consists of: Products (X1), Price (X2), Promotion (X3), Locations (X4), People (X5), Physical Evidence (X6), and Process (X7) on Purchase Decisions (Y) consumers which mediation by consumer trust to use service of JNE Main Branch Medan. The population in this study were 5.400 consumers with 185 samples taken. The research was conducted from August to October 2023. This study used quantitative data which was processed using SEM-PLS analysis model with Smart PLS 3.0. application. Data sources used primary data taken directly from respondents and secondary one was obtained from interviews with JNE Main Branch Management. The results of the research show that product, price, promotion, place, employees, physical evidence, processes and customer trust have a positive and significant effect on customers' purchasing decisions to use JNE Medan Main Branch services. Meanwhile, consumer trust in this research can mediate the influence of product, price, promotion, place, employees, physiscal evidence and processes on customer purchasing decisions at JNE Medan Main Branch